Experimental research on the effect of graphite on heat transfer performance of a latent heat storage system - Zhao, Yuanyuan; Li, Guang; Zhang, Xinzhi; Wu, Hongqiang (Frontiers in Energy Research, 2023)
Phase change materials (PCMs) provide a good resolution for the latent heat storage system which can be used in many application fields such as solar energy utilization and waste heat recovery. This study presents an experimental investigation on the heat transfer performance of paraffin with ceresin (PC) and influence of graphite powder on the thermal characteristics of PC. Water was chosen as the heat transfer fluid. Experimental results showed that the graphite powder increased heating rate of PC and water due to the high thermal conductivity. The time it took for PC to reach the melting temperature was also shortened with different masses of graphite powder, achieving a maximum reduction of 17.2% with 40 g of graphite powder. However, the effect of graphite powder on improving heat transfer efficiency was limited. For 500 g of PC, the promotion effect of graphite powder on heat transfer reached its maximum at around 40 g. Conclusions of this investigation can provide a certain theoretical basis for the design of phase change energy storage systems in applications such as heat pump drying unit, greenhouse energy storage in modern agriculture, solar energy storage utilization technology, and so on.